Antibacterial activity of labdane diterpenoids from Stemodia foliosa - Dantas da Silva, Lourinalda Luiza; Nascimento, Marcia Silva; Cavalheiro, Alberto José [UNESP]; Siqueira Silva, Dulce Helena [UNESP]; Castro-Gamboa, Ian [UNESP]; Furlan, Maysa [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Amer Chemical Soc, 2008)
As part of a continuing interest in exploring the chemistry of Brazilian medicinal plants, three new labdane diterpenoids, 6 alpha-acetoxymanoyl oxide (1), 6 alpha-malonyloxymanoyl oxide (2), and 6 alpha-malonyloxy-n-butyl ester manoyl oxide (3), together with the known betulinic acid, lupeol, sitosterol, and stigmasterol, were isolated from the aerial parts of Stemodia foliosa. The structures of 1-3 were established on the basis of interpretation of spectroscopic data, including HRESIMS, and 1D and 2D NMR techniques. All compounds were tested against a bacteria panel consisting of Staphylococcus aureus, Bacillus cereus, B. subtilis, B. anthracis, Micrococcus luteus, Mycobacterium smegmatis, and M. phlei. Compound 2 showed, moderate activity against these strains, with MIC values in the range 7-20 mu g/mL.